Zinc-bromine flow battery modified diaphragm and preparation method thereof

By modifying the zinc-bromide flow cell separator to improve its hydrophilicity and mechanical properties, the problems of bromide ion shuttle and zinc dendrites in zinc-bromide flow cell are solved, and higher battery performance and longer cycle life are achieved.

CN119852435APending Publication Date: 2025-04-18NANJING TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411810306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Zinc bromine flow batteries face two major technical problems: free shuttle of bromine ions and the formation of negative zinc dendrites during charging.

Method used

By using dopamine to modify the hydrophilicity of the separator, the hydrophilicity of the surface of the separator is significantly improved, the rapid transportation of active substances is promoted, and the average pore size of the membrane is reduced by immersing the dopamine hydrochloride molecule into the pores, inhibiting the free shuttle of bromide ions.

Benefits of technology

It improves the ionic conductivity of zinc-bromide flow batteries, promotes uniform deposition of zinc, extends the cycle life of the battery, and effectively inhibits the free shuttle of bromide ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852435A_ABST
    Figure CN119852435A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-bromine flow battery modified diaphragm which comprises a base diaphragm and a modified layer, the component of the modified layer is dopamine hydrochloride, and a preparation method of the zinc-bromine flow battery modified diaphragm comprises the following steps: S1, preparing a dopamine hydrochloride solution; s2, preparing a modified diaphragm: soaking the base membrane in a dopamine hydrochloride solution, adding a buffer solution, standing, and drying to obtain the modified diaphragm. The hydrophilicity of the diaphragm is improved by using dopamine through a bionic method, alkaline dopamine is very easy to infiltrate through a simple and controllable reaction process, a modified membrane is successfully prepared from a base membrane, the method keeps the original high mechanical property and acid-base stability of the base membrane, the hydrophilicity of the surface of the base membrane is remarkably enhanced, and the service life of the membrane is prolonged. In addition, some dopamine hydrochloride molecules are immersed into holes to reduce the average pore size of the film, so that the free shuttling of bromide ions is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to a zinc-bromine liquid flow battery modified diaphragm and a preparation method thereof. Background Art

[0002] With the depletion of traditional fossil fuels and the booming development of renewable energy power generation, people are paying more and more attention to the research of large-scale energy storage systems. Among the many energy storage technologies, flow battery technology plays an important role in the field of large-scale energy storage technology due to its flexibility in system design and strong scalability. Among the many flow battery systems, zinc-based flow batteries have developed rapidly due to their high energy density and low cost. Zinc-bromine flow batteries (ZBFBs) inherit the advantages of zinc-based flow batteries, use zinc-bromine electrolyte as positive and negative electrodes, avoid the problem of cross-contamination, and have received increasing attention in recent years.

[0003] During the charge and discharge process, zinc ions are deposited and stripped, while bromide ions are combined with complexing agents in the electrolyte and then dispersed. Due to the high solubility of ZnBr2 and the high potential difference between zinc and bromine, the theoretical energy density of ZBFBs can reach 440Wh·kg -1 The actual energy density is about 65-75Wh·kg -1 , much higher than VRFB (25~30Wh·kg -1 ) and ICFB (<10Wh·kg -1 ). However, zinc-bromine flow batteries still face two major technical challenges: one is the free shuttling of bromide ions; the other is the formation of zinc dendrites at the negative electrode during charging.

[0004] Faced with the two major technical challenges of zinc-bromine flow batteries, researchers mainly started from three aspects: improving the electrolyte, designing the electrode structure and composition, and modifying the diaphragm. Adding organic complexing agents to the cathode electrolyte can reduce the activity of bromine in the electrolyte, such as quaternary ammonium salt cations; adding additives to the negative electrode electrolyte can achieve uniform zinc deposition, such as sorbitol additives. In addition, porous carbon electrodes are conducive to the formation of a uniform zinc deposition layer, and can also provide a larger reaction interface for the redox reaction of bromine.

[0005] As one of the key components of ZBFBs, the preparation of battery separators with excellent performance provides another simple and feasible method. Some researchers have achieved rapid ion transport and smoothed the growth of zinc dendrites by designing unique separator structures, such as highly conductive films with continuous water channels, thereby inducing uniform zinc deposition. Some researchers have also suppressed the growth of zinc dendrites by enhancing the mechanical strength of the separator. For example, boron nitride nanosheets with high mechanical strength are used as heat transfer agents and uniformly deposited on porous substrates, thereby preventing the puncture of zinc dendrites and extending the cycle life of zinc-based flow batteries. At the same time, in order to solve the problem of bromide ion shuttling, researchers are increasingly choosing microporous separators with high mechanical strength and low cost as substrates. Smaller pore sizes have good barrier properties for bromine complexes, and the comprehensive performance is optimized by adding functional layers to improve the conductivity of the substrate, such as preparing ion exchange coatings on the surface of microporous separators. These methods are still in the research or preliminary application stage, and the technical maturity is relatively low. Further research and optimization are needed to achieve good results in practical applications. Summary of the invention

[0006] To address the deficiencies of the prior art, the present invention aims to provide a zinc-bromine flow battery modified diaphragm and a preparation method thereof, wherein dopamine is used to modify the hydrophilicity of the diaphragm surface, thereby significantly improving the hydrophilicity, promoting the rapid transport of active substances, and inducing uniform deposition of zinc. The infiltration of dopamine hydrochloride molecules into the pores will reduce the average pore size of the membrane, thereby effectively inhibiting the free shuttling of bromide ions.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A zinc-bromine liquid flow battery modified diaphragm comprises a base film and a modified layer, wherein the modified layer is composed of polydopamine.

[0009] Preferably, the aforementioned base film is one of a PE film, a PP film or a PE / PP composite film.

[0010] The method for preparing a modified diaphragm for a zinc-bromine flow battery comprises the following steps:

[0011] S1. preparing a dopamine hydrochloride solution;

[0012] S2. Preparation of modified diaphragm: Soak the base film in a dopamine hydrochloride solution, add a buffer solution, let it stand, and dry to obtain a modified diaphragm.

[0013] Preferably, the mass ratio of the basement membrane to dopamine hydrochloride is 5:1 to 15:1.

[0014] Preferably, the aforementioned buffer solution is a Tris-HCl buffer solution with a pH of 8.5.

[0015] A zinc-bromine liquid flow battery comprises a positive electrode, a negative electrode and an electrolyte, and also comprises the aforementioned modified diaphragm.

[0016] The benefits of the present invention are as follows: the present invention modifies the hydrophilicity of the diaphragm through dopamine, so that the hydrophilicity of the diaphragm surface is significantly improved, the rapid transport of active substances is promoted, the ion conductivity is improved, and the strong mechanical properties of the membrane itself are maintained, the carrier transport is promoted and the uniform deposition behavior of zinc is induced; in addition, some dopamine hydrochloride molecules are immersed in the pores to reduce the average pore size of the membrane, thereby effectively inhibiting the free shuttling of bromide ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 :(a) Schematic diagram of the preparation steps of PDA@PE membrane;(b) SEM images of original PE membrane and PDA@PE membrane;(c) Fourier transform infrared spectrum;(d) X-ray photoelectron spectroscopy analysis;

[0018] Figure 2 :(a) SEM images of PE films with different coating times in PDA solution;(b) Schematic diagram of surface contact angles of PE films and PDA@PE films;(c) Water absorption of films;(d) Tensile strength histogram of PE films and PDA@PE-24 films;(e) Load-displacement curves of films obtained by nanoindentation test;(f) Thermogravimetric TG curves of PE films and PDA@PE films;(g) Bromide ion permeability of PE films and PDA@PE films;(h) Area specific resistance of PE films and PDA@PE films;

[0019] Figure 3 : Performance diagram of Zn / Br single cell of PE membrane and PDA@PE: (a) Coulombic efficiency of PE membrane and PDA@PE-24 membrane during 80 cycles; (b) Voltage efficiency of PE membrane and PDA@PE-24 membrane; (c) Energy efficiency of PE membrane and PDA@PE-24 membrane; (d) -2 Measurement of the membrane after charging under current; (e) Capacity-voltage curve of PE membrane; (f) Capacity-voltage curve of PDA@PE membrane; (g) Zn-bromine flow battery at 20 mA cm -2 Coulombic efficiency and energy efficiency of PP film and PDA@PE film under current;

[0020] Figure 4 :(a) SEM image of zinc deposition on carbon felt at the end of charging of ZBFBs using PE membrane; (b) SEM image of zinc deposition on carbon felt at the end of charging of ZBFBs using PDA@PE membrane; (c) Wiener scanner scanning results of zinc deposition on carbon felt at the end of cycling of ZBFBs using PE membrane; (d) Micrometer-nanometer scanning results of zinc deposition on carbon felt at the end of cycling of ZBFBs using PDA@PEA membrane;

[0021] Figure 5 It is a schematic diagram of the magnetic pump operating device of the zinc-bromine flow battery;

[0022] Figure 6 are digital photos of the original PE film and PDA@PE film;

[0023] Figure 7 is the element distribution map of the original PE film and PDA@PE;

[0024] Figure 8 It is the Raman spectrum analysis diagram of the original PE film and PDA@PE film;

[0025] Fig. 9 is the pore size diagram of the original PE membrane and PDA@PE membrane by pressure pump method;

[0026] Fig.10 is the Zn / Br single cell performance of PE membranes with different PDA coating times;

[0027] Fig.11 is 20mA·cm -2 SEM images of the PE and PDA@PE membrane surfaces after cycling. DETAILED DESCRIPTION

[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0029] Example

[0030] A modified diaphragm for zinc-bromine flow battery comprises a base film and a modified layer, wherein the modified layer comprises polydopamine. The base film is one of a PE film, a PP film or a PE / PP composite film, and the PE film is selected in this embodiment.

[0031] The method for preparing a modified diaphragm for a zinc-bromine flow battery comprises the following steps:

[0032] S1. Prepare a dopamine hydrochloride solution: dissolve dopamine hydrochloride (PDA) in 500 mL of deionized water to obtain a dopamine hydrochloride solution;

[0033] S2. Preparation of modified diaphragm: Place the treated PE film in a tray containing PDA solution, with a mass ratio of base film to dopamine hydrochloride of 10:1, and add 20 mL of Tris-HCl buffer solution with a pH of 8.5. Let it stand for a while, and finally dry the wet film in air for 24 hours to obtain a modified PDA@PE-x (x represents the standing coating time) film.

[0034] Embodiment Performance Test Method

[0035] 1. Characterization of PDA@PE membrane

[0036] Fourier transform infrared spectroscopy (FTIR) was used for qualitative analysis of multiple samples to identify and confirm the chemical components in the samples. The instrument model used was Thermo Nicolet 8700. The spectra were recorded in the frequency range of 500 to 4000 cm-1, with an average of 32 scans and a resolution of 4 cm-1 to ensure the accuracy and repeatability of the data. The micromorphology of commercial polyethylene film (PE) and polyethylene-based modified films was analyzed using a field emission scanning electron microscope (Hitachi S4800). All film samples were treated with gold spraying for 15 minutes at an accelerating voltage of 3 kV and a current of 5 μA to improve conductivity, and then observed by scanning electron microscopy. Thermogravimetric analysis (TGA) was performed using a NETZSCH STA209F1 thermogravimetric analyzer. The mass of each sample was greater than 10 mg. The experiment was carried out in a nitrogen atmosphere, and the temperature was gradually increased from 25°C to 800°C at a heating rate of 10°C per minute. X-ray photoelectron spectroscopy (XPS) was recorded using a KAlpha spectrometer using a monochromatic X-ray source.

[0037] 2. Tensile strength of membrane

[0038] The tensile strength of the prepared membranes was measured using a tensile tester (HLD 1000, China). Each membrane sample was cut into the same shape (10 mm × 35 mm) using a die cutter, and the thickness of each sample was measured using a thickness gauge. Before the test, the surface water of the sample was wiped with filter paper. In order to reduce the test error, three samples of each membrane were tested. The tensile strength of the membrane was calculated according to the equation:

[0039]

[0040] Among them, F max is the maximum tensile force before the film breaks; W and D are the width (10 mm) and thickness of the film sample, respectively.

[0041] 3. Nanoindentation analysis

[0042] Nanoindentation analysis (Vantage Micromaterials Nanotest, UK) using a conical diamond flat punch (Berkovich type indenter) was performed to investigate the mechanical behavior of the prepared membranes in terms of surface hardness. According to Oliver Pharma analytical techniques, the indentation was performed on an area of ​​2 × 2 cm at room temperature under a maximum load of 5 mN. 2 The film samples were analyzed. In this method, the load was increased linearly for 20 seconds, then kept constant for 10 seconds, and then the load was gradually reduced to 20% of the maximum load (1mN) and held for 20 seconds. Then a second pressurization was performed in the same way, and finally the load was gradually removed completely. Based on these measurements, the load displacement curve was plotted and the surface hardness of the sample was calculated.

[0043] 4. Ionic conductivity (σ) and area resistance (RA)

[0044] The ionic conductivity (σ) and area resistance (RA) of the membrane were measured by the AC impedance method using an electrochemical workstation (Solartron analysis 1470E+1260A, UK). Before the test, the membrane sample was pre-balanced in a 0.5 mol / L NaOH solution for 24 hours. The sample to be tested was clamped between two circular titanium electrodes, and then the sample and the electrode were fixed with a button cell test clip. In the test, the frequency was 1kHz~1MHz and the amplitude was 5mV. The ionic conductivity (σ) and area resistance (RA) of the membrane can be calculated according to the equation:

[0045] σ=L / (R×A); RA=R×A;

[0046] Where L is the thickness of the membrane, R is the resistance of the membrane, and A is the effective area of ​​the membrane.

[0047] 5. ZBFB battery test

[0048] The ZBFB was assembled by sandwiching the membrane between two carbon felt electrodes, which were clamped by two graphite plates, and then all these parts were fixed between two acrylic plates. The active area of ​​the electrodes was 10 × 5 cm 2 A zinc bromide solution consisting of 2 mol / L ZnBr2 is used as the positive and negative electrolytes, and the electrolyte circulates on the positive and negative electrode surfaces through a magnetic pump ( Figure 5 ). During charging, zinc is deposited on the negative electrode, and the bromine produced at the positive electrode is immediately deposited at the bottom of the tank by the bromine complexing agent in the electrolyte. During discharge, the zinc on the surface of the anode dissolves, and the complexed bromine is pumped back into the circulation loop and dispersed, converted into bromide ions, and the electrolyte returns to the state of zinc bromide. The charge and discharge cycle test is performed by ArbinBT 2000. The charging process is determined by the charging time (20mA / cm 2 : 60min) control to maintain a constant charge capacity, and the discharge process is terminated by setting a cut-off voltage of 3V. The coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of the battery are calculated by the following formula:

[0049]

[0050] Example performance test results

[0051] 1. Membrane preparation and morphology

[0052] pass Figure 1 From the SEM image (b), it can be clearly observed that the surface of the dopamine-modified PE film becomes smooth (coating time 24 h). Figure 6 The same results were obtained for the digital photos in .

[0053] In order to verify the successful adhesion of the PDA layer on the PE film surface, the samples were characterized in detail by EDX elemental analysis, Raman spectroscopy, FTIR characterization, and XPS techniques. The results of EDX electronic analysis are shown in Figure 7 The Raman spectroscopy analysis results are shown in Figure 8 As shown in Figure 1, due to the low PDA content, the sensitivity of the first two characterization methods is low. The test results of FTIR are shown in Figure 1. Figure 1 As shown in (c), it can be observed that 3010~2970cm -1 (NH stretching vibration) and 1650-1610cm -1 However, for the original basement membrane and the PDA-modified membrane, the other characteristic peaks of PDA are almost indistinguishable due to the overlap of the peaks. Figure 1 The XPS spectrum in (d) further confirmed the production of PDA. By observing the XPS spectrum, N1s in the range of 396 to 399 eV were detected in the PDA@PE film sample, confirming that PDA was successfully synthesized and attached to the surface of the PE film.

[0054] 2. Performance of PDA@PE membrane

[0055] (1) Effect of coating time on dopamine modification effect

[0056] By adjusting the coating time of PE film in alkaline dopamine solution, a series of PDA@PE-x (x represents time / h) films were prepared. It can be seen intuitively from the SEM images of modified polyethylene films with different coating times, such as Figure 2 As shown in (a), with the increase of dopamine coating, the surface of the film also became smoother, and after 24 hours, the surface structure of the polyethylene film did not change significantly.

[0057] In order to explore the effect of coating time on the modification effect of dopamine, dopamine was mixed with Tris-HCl buffer (PH = 8.5) for 0h, 12h, 24h, 36h and 48h to modify the PE film, and the change of contact angle with coating time was studied. Figure 2 It can be seen from (b) that with the extension of coating time, the contact angle of the film surface shows a trend of first decreasing and then becoming stable. When the reaction time reaches 24h, the surface contact angle has begun to reach 110° and then dropped to the current 81.2°. The surface contact angle is stable at around 80° from 24 to 48h. The results show that when the reaction time is 24h, the dopamine solution achieves the best effect on the hydrophilic modification of the PE film surface. In subsequent experiments, the film with a coating time of 24h was tested.

[0058] (2) Water absorption of the membrane

[0059] In zinc-bromine flow batteries, the water absorption rate (WU) and swelling rate (SR) of the membrane play a key role. WU affects the ion conductivity of the membrane, because the absorption of water is conducive to the migration of carriers, thereby improving the ionic conductivity of the battery. At the same time, SR is directly related to the mechanical stability of the membrane. Too high SR may cause the physical structure of the membrane to be destroyed, forming larger ion transport channels, resulting in the free penetration of a large number of bromide ions, affecting the long-term operation stability of the battery. Therefore, proper control of WU and SR is crucial to ensure the performance and service life of the flow battery.

[0060] like Figure 2 As shown in (c), the water absorption of the dopamine-modified PE film is higher than that of the original PE film, and it increases first and then stabilizes, which is consistent with the previous SEM images and contact angle test results. However, due to its strong mechanical properties, the PE film does not show obvious swelling behavior.

[0061] (3) Mechanical properties of membrane

[0062] The mechanical properties of the membrane determine the structural integrity and compressive resistance of the flow battery during long-term operation, thereby preventing the membrane from rupturing due to electrolyte erosion during operation. This stability is crucial to maintaining the efficient operation of the battery and extending its service life.

[0063] pass Figure 2 (d) It can be seen that the tensile strength of the dopamine-modified PE membrane is better than that of the initial PE membrane. This is due to the full-chain entanglement and mechanical constraint between the rigid polymer chains of PDA and the flexible chains of the PE membrane, which gives the PDA@PE separator higher mechanical properties.

[0064] (4) Thermal stability of the membrane

[0065] The surface hardness of the PDA@PE membrane was tested using nanoindentation technology. The shorter the distance the probe was inserted into the membrane surface, the more difficult it was to penetrate the membrane sample.

[0066] like Figure 2 As shown in (e), after dopamine modification, the displacement of the probe immersed in the PDA@PE membrane is reduced, and the rigid skeleton structure of the surface PDA also increases the surface hardness of the PDA@PE membrane. Figure 2 (f) shows that the addition of PDA has little effect on the thermal stability of PE, and the PDA@PE film exhibits excellent thermal stability.

[0067] (5) Bromide ion permeability of membrane

[0068] The free shuttling behavior of bromide ions in the membrane is one of the important factors affecting the coulombic efficiency and cycle life of zinc-bromine flow batteries. Therefore, the ability of the membrane to inhibit the diffusion behavior of bromide is crucial to improving battery performance. Since dopamine improves the hydrophilicity of the PE membrane surface, it will also penetrate into the pores, resulting in a smaller pore size ( Fig. 9 ). The Br on PE film and PDA@PE film was tested using a diffusion test device. - Ion permeability. Figure 2 As shown in (g), the Br - The ion permeability is lower than that of PE film, which indicates that the binding effect of PDA rigid skeleton on PE flexible chain effectively enhances the barrier capacity of PE film.

[0069] (6) Membrane ionic conductivity

[0070] In addition to bromide ion permeability, the ionic conductivity of the separator is another decisive factor that is crucial to improving the energy conversion efficiency and power of flow batteries. By optimizing the ionic conductivity of the membrane, the overall performance and efficiency of the battery can be significantly improved.

[0071] like Figure 2 As shown in (h), the electrochemical impedance spectroscopy (EIS) test results show that by comparing the resistance of PE film and PDA@PE film, it can be confirmed that the attachment of PDA promotes the rapid transport of H ions.

[0072] 3. Battery performance

[0073] (1) CE, VE and EE of PDA@PE membrane

[0074] During the test, the PE membrane was tested as a control group under the same conditions. Coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) are important bases for judging battery performance. The PDA@PE-x membrane with different reaction times can be tested at 20 mA cm -2 Battery performance at current density.

[0075] like Fig.10As shown in the figure, the CE, VE and EE of the dopamine-modified PE membrane are all improved. First, the increase in CE is due to the pore blockage caused by PDA infiltration, which inhibits the bromide ion shuttle, verifying the results of the ion permeation test and the pressure pump test pore size. Secondly, VE shows a trend of increasing first and then decreasing, and the PDA@PE-24 membrane maintains stability and high voltage efficiency. This is because dopamine will increase the hydrophilicity of the membrane surface in the early stage, promote the transport of active substances, and increase ion conductivity. At the same time, with the continuous increase of dopamine, the pores will be blocked, which is not conducive to circulation, which is consistent with the test results of the contact angle of the membrane surface. Finally, under the condition of higher VE compensation, EE also shows a trend of increasing first and then decreasing. The EE of the PDA@PE-24 membrane reaches the optimal level of 82.2%, which is 5 percentage points higher than that of the PE membrane.

[0076] like Figure 3 As shown in (a) to (c), with the increase of current density, the time of charge and discharge process is shortened, some active ions are not converted, and the internal resistance of the film increases. Then VE decreases, but the decrease of VE is greater than the increase rate of CE, which is manifested as a decrease in EE. -2 The current density not only ensures a higher battery capacity, but also shows a higher battery performance. The modification of dopamine inhibits the shuttling of bromine, which is manifested in high coulombic efficiency, and also promotes the improvement of ionic conductivity, which is manifested in high voltage efficiency.

[0077] (2) Stability of PDA@PE membrane

[0078] The excellent cycle stability of the film is an important indicator for the practical application of ZBFB. According to the above variable current test, the PDA@PE-24 film with the best performance was selected for long-term stability test. During the test, the current density was set to 20 mA cm -2 .

[0079] like Figure 3 As shown in (d), the EE of the PE membrane drops sharply to 60% after 550 h. In contrast, the PDA@PE membrane can operate stably for more than 2000 h, and its EE remains above 75%.

[0080] from Figure 3 From (e) to (f), it can be found that the initial polarization of the PDA@PE film is smaller than that of the PE film. With the accumulation of zinc dendrites, the polarization gradually increases, and eventually the PE film cannot be charged and discharged normally as the number of cycles increases.

[0081] pass Fig.11 It can be seen that the deposition of zinc on the negative electrode carbon felt after long cycles can further confirm that the modification of PDA is conducive to the uniform deposition of zinc.

[0082] like Figure 3As shown in (g), in the self-discharge test, the PDA@PE film exhibits better voltage retention than the PE film. Obviously, the PDA@PE film inhibits the shuttle of bromide ions and reduces the self-discharge phenomenon.

[0083] 4. Effect of PDA coating on zinc deposition behavior

[0084] After the battery has been cycled for a certain period of time, the morphology of zinc deposition on the negative electrode carbon felt is observed. Figure 4 As shown in (a), the zinc deposition on the carbon felt of the battery with PE film presents a large number of typical vertical flaky zinc dendrites, while no obvious sharp zinc deposition is found on the carbon felt of the battery with PDA@PE film ( Figure 4 (b)). In addition, the surface roughness of zinc deposited on carbon felt was evaluated by micro-nano scanning analyzer, which further confirmed that metal zinc was deposited more smoothly on battery carbon felt, and had the coating effect of PDA@PE film on dopamine ( Figure 4 All the above characterizations confirm the excellent advantages of PDA coating in regulating the zinc deposition behavior.

[0085] The present invention uses dopamine to achieve hydrophilic modification of commercial diaphragms. By adjusting the coating time of dopamine, the hydrophilicity of the PE membrane surface is significantly improved, which promotes the rapid transportation of active substances and improves the ionic conductivity while maintaining the strong mechanical properties of the membrane itself. Finally, at a current density of 20 mA cm -2 In the zinc-bromine flow battery, the VE and EE of the PDA@PE-24 membrane reached 83.5% and 79.7% respectively, which are significantly higher than the VE of the pure PE membrane (80.3% and 76.5%). In the long cycle test, the PDA@PE-24 film ran smoothly for more than 2000 hours, which is four times that of the PE film, and there was no obvious performance degradation.

[0086] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A modified diaphragm for zinc-bromine flow battery, characterized in that: The invention comprises a base film and a modified layer, wherein the modified layer is composed of polydopamine.

2. A zinc-bromine flow battery modified diaphragm according to claim 1, characterized in that: The base film is one of a PE film, a PP film or a PE / PP composite film.

3. The method for preparing the modified diaphragm according to claim 1, characterized in that: The following steps are involved: S1. preparing a dopamine hydrochloride solution; S2. Preparation of modified diaphragm: Soak the base film in a dopamine hydrochloride solution, add a buffer solution, let it stand, and dry to obtain a modified diaphragm.

4. The method for preparing the modified diaphragm according to claim 3, characterized in that: The mass ratio of the basement membrane to dopamine hydrochloride is 5:1 to 15:

1.

5. The method for preparing the modified diaphragm according to claim 3, characterized in that: The basement membrane is immersed in the dopamine hydrochloride solution for 12 to 48 hours.

6. A zinc-bromine flow battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: Also included is the modified diaphragm as described in claim 1.

Citation Information

Cited By

  • Functional diaphragm applied to bromine-based flow battery and preparation method of functional diaphragm

    CN121149325A

  • Functionalized separator for application in bromine-based flow batteries and method for its preparation

    CN121149325B